Livelihood Option through Trout Seed Production in Jammu and Kashmir: An Economic Analysis - Gawa, Stanzin; Kumar, Nalini Ranjan; Mahida, Navghan; Hatte, Vinay Maruti (Fishery Technology, 2017)
The present study was conducted during the period2014-15 to understand the economics of trout seedproduction in the state of Jammu and Kashmir. Itwas observed that the trout seed production is acapital intensive business, with high cost involvedin the establishment of fixed inventories. The studyshowed that 79.65% of seed produced in the stateis used for culture purpose while 20.35% is utilizedto stock the springs and streams for sports fisheries.The major capital investment was incurred inhatchery construction (around 90 lakh), whichaccounted 72.25% of the total capital investment.Cost and return analysis revealed fixed cost about` 55.24 lakh and variable cost about ` 2.42 lakhwhich accounted about 95.63 and 4.37% respectively.The major constraints encountered in trout seedproduction was lack of skill labour and low demandfor trout seed. Due to low demand for trout seedthe trout hatcheries were running at a sub-optimallevel but the demand for trout seed is expected torise with increasing number of private trout farmers.With proper skill enhancement the trout hatcherybusiness can transform into a viable livelihoodoption for entrepreneurs.